Research on the Properties of Nano-Al2O3- and Nano-SiO2-Modified Bio-Asphalt and Mixtures - Wei Qiao; Feilong Yuan; Xiaojian Xu; Qingzhou Wang (Buildings)
Bio-oil as a substitute or modifier for petroleum asphalt has significant environmental, economic, and sustainable development implications. However, the insufficient high-temperature and anti-aging characteristics of bio-asphalt lead to the limited application of bio-oil in road engineering. In this study, the characteristics of bio-asphalt were reinforced by nano-Al2O3 and nano-SiO2. The nanomaterial-modified bio-asphalt was evaluated using basic characteristics, viscosity, and high- and low-temperature rheological characteristic tests. Meanwhile, the road behavior of nanomaterial-modified bio-asphalt mixtures was assessed. The test results demonstrated that incorporating bio-oil improved the low-temperature performance of PA. Compared with PA, BA’s ductility was increased by 83.87%. Nano-Al2O3 and nano-SiO2 positively affected the bio-asphalt’s temperature sensitivity and high-temperature and anti-aging characteristics but inhibited the low-temperature characteristics. Combining the results of the high- and low-temperature characteristics of nanomaterial-modified bio-asphalt, a nano-Al2O3 dosage between 4 and 6% or a nano-SiO2 dosage between 6 and 8% can realize the enhancement of high-temperature and anti-aging characteristics of bio-asphalt, and the low-temperature characteristics are better than those of petroleum asphalt. Meanwhile, the dynamic stability, crack resistance, and water loss resistance of the nanomaterial-modified bio-asphalt mixtures meet the specification requirements. The adjustable and designable high- and low-temperature characteristics of bio-asphalt can be realized by adjusting the dosage of nanomaterials. The application of bio-oil and nanomaterials promotes the resourceful utilization of waste and provides new possibilities for road engineering materials.